2017
DOI: 10.1007/s10295-016-1873-0
|View full text |Cite
|
Sign up to set email alerts
|

Pectinase production by Aspergillus giganteus in solid-state fermentation: optimization, scale-up, biochemical characterization and its application in olive-oil extraction

Abstract: The application of pectinases in industrial olive-oil processes is restricted by its production cost. Consequently, new fungal strains able to produce higher pectinase titers are required. The aim of this work was to study the capability of Aspergillus giganteus NRRL10 to produce pectinolytic enzymes by SSF and evaluate the application of these in olive-oil extraction. A. giganteus was selected among 12 strains on the basis of high pectinolytic activity and stability. A mixture composed by wheat bran, orange, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 41 publications
(64 reference statements)
0
16
0
2
Order By: Relevance
“…Vol.63: e20190515, 2020 www.scielo.br/babt frigidphilos profundus, whereas Fe +3 and Ca +2 showed less effect [50].According to Ortiz and coauthors, an increase in K2HPO4, traces solutions and Ca+2 factors exerts a positive effect on PGase production by Aspergillus giganteus NRRL10. Yeast extract, and Fe +2 had insignificant effect on enzyme productivity [51]. Poondla and coauthors studied the influence of different metal ions in the production of PGase by Saccharomyces cerevisiae, the production of enzymes increased considerably with MnSO4> KH2PO4> ZnSO4> CaCl2> MgSO4> CoCl2 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Vol.63: e20190515, 2020 www.scielo.br/babt frigidphilos profundus, whereas Fe +3 and Ca +2 showed less effect [50].According to Ortiz and coauthors, an increase in K2HPO4, traces solutions and Ca+2 factors exerts a positive effect on PGase production by Aspergillus giganteus NRRL10. Yeast extract, and Fe +2 had insignificant effect on enzyme productivity [51]. Poondla and coauthors studied the influence of different metal ions in the production of PGase by Saccharomyces cerevisiae, the production of enzymes increased considerably with MnSO4> KH2PO4> ZnSO4> CaCl2> MgSO4> CoCl2 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Jahan et al (2017) reported high yield of polygalacturonase in fermentation broth having 1.0% wheat bran as a substrate Zapata and Voget (2012) supplemented with NaNO 3 and yeast extract as source of nitrogen and KH 2 PO 4 was selected as suitable micronutrient. Wheat bran along with orange peel and lemon peels has been reported as best substrate combination for pectinase production by Aspergillus giganteus NRRL10 (Ortiz et al 2017). Demir and Tari (2016) have reported the effect of moisture content on wheat bran thickness, which affects polygalacturonase production in SSF.…”
Section: Crop Wastementioning
confidence: 99%
“…Pectinases are composed of depolymerizing enzymes such as polygalacturonase (EC 3.2.1), pectin lyase (EC 4.2.2) and decomposting enzymes such as pectin esterase (EC 3.1.1). They have been used for extraction and clarification of fruit juices and wines, maceration of tea leaves and increase the juice and oil extraction yields as well as various biotechnological processes (Ortiz et al 2017). Another important enyzme for the food industry is tannase or tannin acyl hydrolase (EC 3.1.1.20) that catalyses the breakdown of hydrolyzable tannins or gallic acid esters to release glucose and gallic acid.…”
Section: Introductionmentioning
confidence: 99%